ELABORASI TEKNIK MEMPEROLEH NASABAH PEMBIAYAAN YANG SEHAT - Heru Setiawan; Nina Maulina Supriyanto; Kharis Fadlullah Hana (Prodi Perbankan Syariah FEBI UIN Ar-Raniry, 2022)
Banks always evaluate prospective customers before offering financing to customers, so there are several principles to evaluate and to get healthy financing customers at the bank. The purpose of this study is to obtain healthy financing customers. This research uses qualitative methods by employing an interview method. Data is collected through interviews with employees and customers who use Indonesian Islamic banks. The results of this study show the discussion of techniques for obtaining healthy financing customers through a door-to-door survey of the customer's business premises, advertisements and excellent service and others. The research also recommends Islamic banks in Indonesia to improve financing survey to customers